157 Treatment-Refractory Mania With Psychosis in Post-Transplant Patient on Tacrolimus: A Case Report. (15th June 2018) - Bordoloi, Meelie; Singh, Garima; Ithman, Muaid Hilmi
Abstract : Abstract: We present a case of a 66 year old Caucasian female with Bipolar type 1 disorder, status post right renal transplant (5/8/14) on maintenance immunosuppression who presented with mania and psychosis. The previous weeks had her being sleep deprived, talkative, making random calls to family members at odd hours, demonstrating pressured speech and also having erotomania regarding Joshua Bell, the violinist. She had recently been switched from Divalproex sodium (on which she had been stable for years) to Quetiapine due to thrombocytopenia attributed to the former. Quetiapine was optimized to 800 mg over two weeks without any improvement. She continued to be severely manic with new delusions of being in a World War II zone and the staff being NAZIs. She continued to be tangential with disorganized behavior and inability to care for self. She was then restarted on Divalproex sodium (for mood) with close monitoring of her counts along with Risperidone (for psychosis). Divalproex sodium was optimized to 1500mg and Risperidone to 6 mg over the next 2 weeks without much improvement. Risperidone was then cross tapered with Olanzepine. We also began to pursue other causes of treatment refractory mania withpsychosis, namely her immunosuppressant medications. She had been placed on maintenance immunosuppression withtacrolimus (Prograf) 3mg BID, Mycophenolic acid (Myfortic) 360 mg BID and Prednisone 5 mg. Though the most recent Tacrolimus level was within therapeutic range, they were still higher than her baseline levels. Based on few case reports of psychosis associated with Tacrolimus and per discussion with nephrology, we planned cross taper of Tacrolimus and Cyclosporin. Tacrolimus was eventually tapered off and Cyclosporine was maintained at 125 mg qam and 100 mg qpm. Prednisone was maintained at 5 mg daily. Her mania and psychosis improved and she was ultimately discharged on Olanzepine 20mg qhs, Divalproex sodium 1500mg qhs, The problems encountered during this case were plenty due to multiple comorbid conditions including a right adrenal adenoma, hypertension, impaired glucose tolerance, thyroid dysfunction, hyperlipidemia and having bio-prosthetic aortic valve due to Aortic stenosis (2013). In conclusion, psychosis can be precipitated in renal transplant patient with Bipolar disorder I with previously maintained stability on Tacrolimus with other comorbid conditions. So, It would be important to re-evaluate the use of Tacrolimus or the possibility of switching to another immunosuppressive agent withcareful consideration of risks versus benefits. Case management should include good coordination of care with Family medicine, Transplant/nephrology team and social services for efficacious and successful management of patient. Funding Acknowledgements: No funding.